TEACHER - Arvydas Šliogeris (Problemos)
The article is about Prof. E. Meškauskas as a person. The author of the article who was a disciple and younger colleque of Prof. E. Meškauskas tells how Prof. E. Meškauskas disclosed himself as a person brightly in the spontaneity of the Socratic dialoque liberating the mind of his disciple too.